A vertical oligopoly in which entry increases every firm's profit. Issue 3 (8th April 2021) - Nariu, Tatsuhiko; Flath, David; Okamura, Makoto
Abstract: We develop a model in which each of m manufacturers forms a differentiated final product by assembling n components that are provided by its own n independent suppliers. Each supplier produces a unique component and sells to only one of the manufacturers. The manufacturers engage in product‐differentiated Cournot competition. We show that if initially the number of manufacturers is sufficiently small, and if the number of components is large enough, then, as the number of manufacturers increases, every firm—including downstream manufacturers and their upstream component suppliers—earns more profit. Entry can increase every firm's profit. The package‐tour industry of Japan is an example of such an industry. Drip coffee supplied by competing convenience stores in Japan is another.